Trends in Brazilian market of antidepressants: A five-year dataset analysis - Hoefler, Rogério; Galvão, Taís Freire; Ribeiro-Vaz, Inês; Silva, Marcus Tolentino (Frontiers in Pharmacology, 2022)
Introduction Depression is a mental disturb associated with morbidities and disabilities worldwide. The growing use of antidepressants is a concern for health managers because still unanswered questions on the effectiveness and safety of these medicines. The general Brazilian pharmaceutical market has increased last years, but we have not found published data on the antidepressants sales. We described the trends in the antidepressant commerce in Brazil in a five-years period. Materials and Methods We performed an ecological study on antidepressant sales in Brazil, from November-2014 to October-2019, using data from IQVIA™. Antidepressants were coded by Anatomical Therapeutic Chemical classification system; sales were presented in defined daily doses (DDDs) and DDDs per 1,000 inhabitants per day (DIDs). Results were expressed in absolute quantities and growth rates. Results The analyzed dataset contained 23 active substances in 780 products. The total sales of antidepressants rose from 23.3 DIDs to 38.3 DIDs in the period (p = 0.002). Selective serotonin reuptake inhibitors were the most sold class (+5.7 million DDDs) in the period. The class ‘other’ antidepressants presented the largest growth rate (104.7%). Individually, the most sold active substance was escitalopram (+1.8 million DDDs) and vortioxetine had the largest growth rate (336.2%). Tricyclics sales remained unchanged and monoamine oxidase inhibitors had low and even falling sales (-9.5%). Discussion The total sales of antidepressants increased in Brazil from November 2014 to October 2019. The higher sales volumes of selective serotonin reuptake inhibitors and higher growth rate of ‘other’ antidepressants, with low sales volume of tricyclics and a decrease of monoamine oxidase inhibitors suggest the replacement of older drugs by the newer ones following a global trend. Therapeutic advances and promotion efforts on new products might explain these observations. Further investigations might analyze associations among the observed variations and some factors, in order to clarify the reasons for the sales trends of these drugs in Brazil.